Lecturer self-efficacy beliefs: an integrative review and synthesis of relevant literature - Matos, Mayara da Mota [UNESP]; Iaochite, Roberto T. [UNESP]; Sharp, John G. (Taylor & Francis, 2021)
This article reviews available research literature in the field of lecturer self-efficacy beliefs produced between 1988 and 2020. Given the growing interest in lecturer self-efficacy beliefs in recent years, and the global challenges the Higher Education sector will face following the current Covid-19 pandemic, the time to conduct such a review seems appropriate. Fifty-five empirical papers in English, Spanish and Portuguese were identified and examined. Findings show that papers investigated the beliefs of lecturers from 23 countries using mostly quantitative cross-sectional approaches involving questionnaires. Among the eight main themes that emerged, ‘teaching self-efficacy’ featured prominently and received most attention, while other aspects of the work of lecturers, including research, service-related and other administrative activities, were also considered. Concerning personal variables like gender, there was no consensus over whether different characteristics affected self-efficacy beliefs more than others. Conclusions point to the need for additional mixed-methods and qualitative studies with more refined and contextualised methodological approaches to better understand the field, to identify actual sources of self-efficacy themselves and to more fully inform policy, practice, the distribution of resources and building capacity.
Keywords: Higher Education; Lecturer self-efficacy; professional development; research; service-related activity; teaching